2020
DOI: 10.1186/s12884-020-02907-x
|View full text |Cite
|
Sign up to set email alerts
|

Social concerns related to HIV status disclosure and participation in the prevention of mother-to-child transmission of HIV care among pregnant women in Kenya

Abstract: Background: Social concerns about unintentional HIV status disclosure and HIV-related stigma are barriers to pregnant women's access to prevention of mother-to-child transmission of HIV (PMTCT) care. There is limited quantitative evidence of women's social and emotional barriers to PMTCT care and HIV disclosure. We aimed to investigate how social concerns related to participation in PMTCT care are associated with HIV status disclosure to partners and relatives among pregnant women living with HIV in western Ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 43 publications
4
12
1
Order By: Relevance
“…Other possible reasons are lower barriers to testing due improved partner disclosure of HIV status and diminished concerns of intimate partner violence 36 . We have previously observed that pregnant women in this study setting are more willing to disclose their HIV status to a current partner 37 compared to earlier studies 38 44 , which is consistent with other recently published studies from Kenya 45 47 , indicating a potential positive move forward towards more openness between partners. We have also reported on reduced concerns of intimate partner violence related to women’s participation in PMTCT care in the study area 37 .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Other possible reasons are lower barriers to testing due improved partner disclosure of HIV status and diminished concerns of intimate partner violence 36 . We have previously observed that pregnant women in this study setting are more willing to disclose their HIV status to a current partner 37 compared to earlier studies 38 44 , which is consistent with other recently published studies from Kenya 45 47 , indicating a potential positive move forward towards more openness between partners. We have also reported on reduced concerns of intimate partner violence related to women’s participation in PMTCT care in the study area 37 .…”
Section: Discussionsupporting
confidence: 91%
“…We have previously observed that pregnant women in this study setting are more willing to disclose their HIV status to a current partner 37 compared to earlier studies 38 44 , which is consistent with other recently published studies from Kenya 45 47 , indicating a potential positive move forward towards more openness between partners. We have also reported on reduced concerns of intimate partner violence related to women’s participation in PMTCT care in the study area 37 . Moreover, the proportion of infants diagnosed with HIV by eight weeks of age in our trial was only 1.0%, which is much lower than the national EID HIV transmission rate (5%) by eight weeks of age among HIV-exposed infants in 2019 1 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The analysis of this study shows that the prevalence of status disclosure to partners among HIV-positive women who were older than 18 years is 85.2%. The findings of this study are similar to disclosure rates in studies carried out in Uganda and Kenya reporting 85.4% and 80% HIV-status disclosure rates by women to their male partners, respectively [ 34 , 35 ]. Conversely, the prevalence observed in this study is higher compared to previous studies conducted in Uganda (57%) and Tanzania (66%) [ 34 , 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…Results from a meta-analysis found that more than 67% of pregnant women in sub-Saharan Africa had disclosed their HIV status 17. Increased disclosure rates were also evident in subsequent studies conducted after 2015, with disclosure rates of 80%, 85%, 94.9% and 99% in Kenya, Nigeria, Malawi and Uganda, respectively6 18–21 and disclosure to male partners was more evident than disclosure to family members 6 17 19. According to Bucagu et al ,21 HIV status disclosure is more frequent in women than in men and disclosure is generally higher in steady partners than in casual partners.…”
Section: Introductionmentioning
confidence: 99%